POLA PERKEMBANGAN KOTA PEKANBARU DAN FAKTOR YANG MEMPENGARUHINYA - Veronicha Briliani; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
The built-up area in Pekanbaru City is increasing every year. Changes in land use in Pekanbaru City are dominated by the conversion of non-urban land uses, namely forests, plantations, and shrubs into urban land uses (built areas). This study aims to determine the development pattern of Pekanbaru City by using spatial matrix analysis and the factors that influence the development of Pekanbaru City using the cellular automata method used in experimental modeling. The pattern of development using the spatial matrix method was quantified using Arcgis and Fragstats software software. The results of the processing of changes in the built area of Pekanbaru City have increased every year. As for the pattern of urban development, it can be concluded based on the findings of research conducted using spatial matrices. The matrices used are NP, PD, LPI, LSI, MPS, SHDI, and SHEI. Pekanbaru City based on calculations has a pattern that is fragmented or tends to spread (Sprawl). Pekanbaru city is influenced by several driving factors, namely accessibility which consists of distance to primary roads, distance to secondary roads and distance to settlements. In this study, LanduseSim software was used to simulate land development in Pekanbaru City to see the effect of the simulated driving factor.